Influence of lead in the sorption of arsenate by municipal solid waste composts: metal(loid) retention, desorption and phytotoxicity. (February 2017) - Silvetti, Margherita; Garau, Giovanni; Demurtas, Daniela; Marceddu, Salvatore; Deiana, Salvatore; Castaldi, Paola
Highlights: MSW-composts were able to sorb As(V) at acidic pH only when Pb(II) was present. Pb(II) and As(V) were simultaneously sorbed by the MSW-composts investigated. Sequential extraction indicated different interactions between As(V) and Pb(II). As(V) phytotoxicity was buffered by MSW-composts when Pb(II) was present. Abstract: The ability of two municipal solid waste composts (MSW-C) to sorb As(V) in the presence of Pb(II) and in acidic conditions was investigated. Sorption isotherms and kinetics showed that both MSW-C were able to sorb As(V) in a similar way (∼0.24 mmol g −1 MSW-C), but only when Pb(II) was present (0.45 mmol L −1 ). The concomitant sorption of Pb(II) by both MSW-C (∼0.40 mmol g −1 ) suggested that the metal cation was likely acting as bridging element between the negatively charged functional groups of composts and As(V). SEM-EDX analysis of the MSW-C + Pb(II) + As(V) systems supported the association between Pb(II) and As(V), while sequential extraction procedures and organic acids treatment showed that As(V) was strongly retained by MSW-C + Pb(II) and suggested the presence of different interaction types between As(V) and Pb(II). Plant growth experiments highlighted the key role of Pb(II) in the reduction of As(V)-phytotoxicity for triticale plants (× Triticosecale Wittm.) in the presence of MSW-C.